Drawing a line between the religious and the secular: the cases of religious education in Sweden and India - Niemi, Kristian (Journal of beliefs and values, 2018)
Religion as a school subject - Religious Education (RE) - is handled differently in various national contexts. This article discusses two different systems of managing (or avoiding) RE: those used in non-denominational Swedish and Indian schools. The article focuses particularly on what is allowed in the classroom with regards to religion. Both countries are secular, but where is the line drawn between the secular and the religious? Allowing the two contexts to meet reveals the particularities of each. The impact of Protestant Christianity, specifically Lutheranism, is evident in Swedish RE: religion is to be defined through beliefs and words, and religious actions should be excluded from classrooms. The Swedish context highlights knowledge of' religions, but avoids religious action. In India, there is no explicit RE, but Indian education does include learning from religion as well as doing religion.' The Indian approach is very inclusive, to the point of emphasising, as teachers put it, a common core of all religions. Both systems of RE offer particular opportunities and face certain difficulties in dealing with the contemporary globalised world.